2011
DOI: 10.1590/s0104-11692011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, happiness and satisfaction with life of individuals 75 years old or older cared for by a home health care program

Abstract: This case study identifies the elements that compose the Quality of Life (QofL) of individuals who were 75 years old or older and receive care at home. The study's sample was composed of individuals 75 years or older cared for by a home health care service in the primary health care unit in Vilafranca del Penedès, Spain (n=26). The variables included: a) socio- As variáveis foram: a) dados sociodemográficos, b) conceito de QV, c) percepção de QV, d) motivos, e) satisfação com a vida e aspectos relacionados e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…It is possible to note a larger number of patients registered in the administrative regions of Sobradinho (1994), Planaltina (1997) and Gama (2002), who were the first nuclei to be implemented, hence the oldest, and in the most populated administrative regions of Ceilândia (414.531 inhabitants) and Samambaia (205.516 inhabitants), despite these being newer sites, implemented in 2009. The age and gender distribution of assisted patients (Table 2) showed similar profiles to the population of most of the studied services, either national, with the family health strategy and the home care teams (Martos and Sanches, 2009;Marques and Freitas, 2009;Marin et al, 2010;Del Duca et al, 2012), or international (Genet el al., 2011;Llobet et al, 2011;Jones et al, 2012), which is in agreement with data from the Brazilian Institute of Geography and Statistics (IBGE -Instituto Brasileiro de Geografia e Estatística) (IBGE, 2014). It states the age of 80 years or older with the highest growth rates among the elderly, higher incidence of chronic diseases, poorer functional capacity, lesser autonomy, requiring more attention from the family and society, and greater predominance of women.…”
Section: Resultssupporting
confidence: 83%
“…It is possible to note a larger number of patients registered in the administrative regions of Sobradinho (1994), Planaltina (1997) and Gama (2002), who were the first nuclei to be implemented, hence the oldest, and in the most populated administrative regions of Ceilândia (414.531 inhabitants) and Samambaia (205.516 inhabitants), despite these being newer sites, implemented in 2009. The age and gender distribution of assisted patients (Table 2) showed similar profiles to the population of most of the studied services, either national, with the family health strategy and the home care teams (Martos and Sanches, 2009;Marques and Freitas, 2009;Marin et al, 2010;Del Duca et al, 2012), or international (Genet el al., 2011;Llobet et al, 2011;Jones et al, 2012), which is in agreement with data from the Brazilian Institute of Geography and Statistics (IBGE -Instituto Brasileiro de Geografia e Estatística) (IBGE, 2014). It states the age of 80 years or older with the highest growth rates among the elderly, higher incidence of chronic diseases, poorer functional capacity, lesser autonomy, requiring more attention from the family and society, and greater predominance of women.…”
Section: Resultssupporting
confidence: 83%
“…In the same way that improvement in psychological variables can increase success in exhibiting personal independence, compatibility between the environment and the individual can improve or decrease the performance of the activity, leading him or her it to finish the activity or not (Llobet, Avila, Farrás Farrás, & Lluch Canut, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In an American study on disability, participation and subjective wellbeing in older adults, findings showed that people who reported disability presented significantly lower scores than people without alterations. 15 The literature refers that physical impediments play a determinant role in health assessment and, therefore, in the wellbeing of older adults. 4 In line with these results, in a study developed in Brazil, which related functional capacity with quality of life, older adults with a higher level of functional disabilities presented lower quality of life scores than people without functional alterations.…”
Section: Discussionmentioning
confidence: 99%